Water Stress: installation of a Community Water Tank in Los Cedros Neighborhood in Paraná - Gastiazoro, Tomás; Vivas, Constanza (My University, 2022)
Summary— In this work we are going to address a highly frequent problem in the city of Paraná, which is water stress. This problem mainly occurs in the highest areas of the city. Los Cedros neighborhood generally faces this situation. The purpose of this work is to sort out the low water pressure problem in Los Cedros neighborhood in the city of Paraná. To fulfill this aim, we are going to propose the installation of a community storage tank in a strategic point of the neighborhood. Resumen— En este trabajo vamos a abordar un problema muy frecuente en la ciudad de Paraná, que es el estrés hídrico. Este problema se presenta principalmente en las zonas más altas de la ciudad. El barrio Los Cedros generalmente enfrenta esta situación. El objetivo de este trabajo es solucionar el problema de baja presión de agua en el barrio Los Cedros de la ciudad de Paraná. Para cumplir con este objetivo, vamos a proponer la instalación de un tanque de almacenamiento comunitario en un punto estratégico del barrio.
Keywords: Estrés hídrico; Water Stress; Tanque en Barrio Los Cedros en Paraná; Tank in Los Cedros Neighborhood in Paraná; sistema comunitario de agua; Community Water; Agua comunitaria